An Analysis of Student Vocabulary in Finding Noun Trought Descriptive Text at SDN 013 Laboy Jaya - Musyafii, Husen; Sari, Nurhidayah (Journal of English Language and Education, 2024)
Vocabulary is a basic skill that must be mastered in learning and mastering English. Vocabulary will relate to four skills in English, namely reading, listening, writing, and speaking. Vocabulary has several types, one of which is a noun. This research will focus on describing an analysis of student vocabulary in finding noun through descriptive text at SDN 013 laboy jaya bangkinang in the 2022/2023 academic year. This study aims to determine the student's English vocabulary in finding nouns through descriptive text. Researchers chose class iv SDN 013 laboy jaya bangkinang as many as 24 students as samples in this study. In this study, researchers used tests, observations and documentation in collecting data. Based on the research findings, the researcher found that the test results for the students were good. As many as 10 students get very good score criteria, 3 students get good score criteria, 6 students get enough, and 5 students get low score criteria in the test. The range of scores shows that the average student test score is 70. The criteria for this score are taken from (arikunto, 2009) where a score of 70-79 indicates good or well.